Eye Blinks as an Indicator of Car Drivers’ Visual Attention: A statistical analysis of differences in eye blinks between roads of high and low complexity - Ek, Paula; Österberg, Felicia (My University, 2021)
The majority of all traffic crashes occur due to human error, according to National Highway Traffic Safety Administration. As the development of self-driving vehicles´ progress, the driver's role changes to a more monitoring nature, successively eliminating the effect of human error. However, until fully automated vehicles are achieved, the driver needs to be ready to take control over the vehicle in critical situations. Therefore, visual attention is an important attribute to be a reliable car driver engaged in the traffic environment. The thesis sets out to investigate the usability of human eye blinks as an indicator of car drivers´ visual attention. The investigation is based on electrooculography (EOG) measurements obtained during an on-road experiment performed by Volvo Cars and Research Institutes of Sweden (RISE). The data is used to analyse differences in blink rate and half blink duration between interchange (high demand of attention) and motorway (low demand of attention). Surprisingly, the results indicate that the blink rate increases during interchanges, which contradicts findings from previous studies. The contradiction derives from an increase in blink-saccadic pairs occurring due to the driving behaviour in interchanges. \\ Additionally, the result implies that half blink duration increases during motorways. From the findings, it is concluded that blinks without large saccadic eye movements are less affected by driving behaviour and could therefore be a potential robust indicator of visual attention. Further, half blink duration is a possible indicator to measure a drivers' visual attention. Therefore, eye blink measurements have the potential to alert vehicle safety systems about the driver´s level of engagement.
Keywords: Eye blinks; Visual attention; Blink rate; Half blink duration; Road complexity